Understanding the Characteristics of Salihah Women as the World’s Best Jewelry in the Perspective of Hadith: A Study of Takhrij and Syarah Hadith - Abdul Qodir, Ilham Musthofa; Zuhdi, Muhammad (Journal of Takhrij Al-Hadith, 2023)
This study aims to discuss the hadith about the characteristics of pious women. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the characteristics of pious women in the history of Imam Ahmad No. 6279. The results and discussion of this study indicate that the status of quality hadith is shahihthat meets the qualifications of maqbul ma’mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 6279 is relevant to be used as motivation to develop yourself into a pious woman. Â